188 INFUSIONAL ETOPOSIDE, DAUNORUBICIN, VINCRISTINE, AND CYTARABINE IN RELAPSED ACUTE MYELOGENOUS LEUKEMIA. (1st January 2006) - Walker, B.; Elkins, S.; Bigelow, C.; Files, J.
Abstract : Background: The likelihood of achieving a second remission in relapsed acute myelogenous leukemia (AML) is directly related to the duration of the first remission. Patients with relapses within the first year or those with refractory disease do especially poorly, with complete response (CR) rates of 10-20%. Salvage regimens using agents such as high-dose cytarabine have frequently been used, but second remissions are brief and treatment-related mortality is 20-25%. Methods: We report a retrospective review of 24 patients with AML who were refractory to induction therapy or relapsed within 12 months of induction therapy. These patients received cytarabine 150 mg/m 2 IV CI on days 1-7, etoposide 100 mg/m 2 IV CI on days 3-7, daunorubicin 20 mg/m 2 IV CI on days 4-7 and vincristine 0.8 mg IV CI on days 4-7. Results: There were eight complete remissions for a CR rate of 33% and median time to relapse of 5 months. The 30-day mortality rate was 4.2%. A total of 9 patients over 50 years old were included with 4 complete responses for a CR rate of 44%, and none died in the first 30 days. Conclusion: This regimen produced a good remission rate for these poor-risk patients with less treatment-related mortality than conventional treatment. In the small subset of patients under 50 years old, efficacy was shown, as well as tolerability. With the age at onset in AML increasing, therapies are needed that attain a CR with low treatment-related mortality.